BAMBOO SHELTER STRUCTURAL DESIGN OPTIMIZATION: TOWARD SUSTAINABLE DISASTER RELIEF HOUSING - I Ketut Yasa Bagiarta; I Nengah Sinarta; Putu Didik Sulistiana (Journal of Infrastructure Planning and Engineering, 2025)
This study explores the optimization of bamboo shelter design for emergency housing by integrating technical, implementation, and sustainability aspects in Karangasem Regency, Bali. Using a literature review approach combined with comparative and evaluative analysis, the research examines the structural properties of bamboo compared to conventional materials, assesses joint systems, and evaluates the proposed shelter design from a sustainability perspective. The findings highlight bamboo’s key advantages, including rapid construction time (approximately one week per unit) and cost efficiency (Rp1,500,000–Rp4,500,000 per shelter). The proposed design results in a low carbon footprint of 22 kg CO2/year/m2 and demonstrates a CO2 absorption capacity of 3,260 kg/year. Sustainability assessment indicates strong performance in technical reliability (score 4) and shelter habitability (score 4), moderate results in CO2 emission mitigation and affordability (score 3), and room for improvement in material efficiency (score 2) and tree protection (score 1). This research provides a foundation for developing sustainable bamboo shelters that balance structural performance, environmental impact, and socio-economic feasibility in post-disaster contexts.